2015
DOI: 10.1126/sciadv.1500390
|View full text |Cite
|
Sign up to set email alerts
|

Near-IR squaraine dye–loaded gated periodic mesoporous organosilica for photo-oxidation of phenol in a continuous-flow device

Abstract: A study of dye-loaded organosilica for photo-oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…We also investigated the potential use of our approach for the synthesis of adaptive composites or responsive soft devices . The cascade reaction system based on MSN/TA–Cu II was further coupled with an acid‐degradable hydrogel consisting of polyvinyl alcohol (PVA) and borax.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…We also investigated the potential use of our approach for the synthesis of adaptive composites or responsive soft devices . The cascade reaction system based on MSN/TA–Cu II was further coupled with an acid‐degradable hydrogel consisting of polyvinyl alcohol (PVA) and borax.…”
Section: Figurementioning
confidence: 99%
“…Owing to the possibility to further functionalize TA with thiols, we believe that it should be possible to form functionalized nanocontainers from our nanocontainers in the future. According to the strategy described herein, judicious combinations of functionalities and materials will lead to advances in adaptive composites and materials science …”
Section: Figurementioning
confidence: 99%
“…Interestingly,F E-SEM revealed that the MSN/TA-Cu II particles were still packed on the substrate after light exposure;t his was employed to decompose the metal complex (Figure 4d). [18,19,[37][38][39][40][41][42] Thec ascade reaction system based on MSN/TA-Cu II was further coupled with an acid-degradable hydrogel consisting of polyvinyl alcohol (PVA) and borax. This might allow them to keep their original arrangement.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[34] We also investigated the potential use of our approach for the synthesis of adaptive composites or responsive soft devices. [18,19,[37][38][39][40][41][42] Thec ascade reaction system based on MSN/TA-Cu II was further coupled with an acid-degradable hydrogel consisting of polyvinyl alcohol (PVA) and borax. Upon exposure to light, the PAGs triggered the decomposition of the TA-Cu II complexes as well as the gel network, resulting in as ignificant release of RB molecules and accelerated decomposition of the hydrogel in distilled water ( Figure 5).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation